KADAR TSH DI MuLTIDRuG ReSISTAnCe TuBeRCuLoSIS TERKAIT ETIONAMID - Suparyatmo Suparyatmo; B. Rina A.S; Harsini Harsini; Musayadah Musayadah (INDONESIAN JOURNAL OF CLINICAL PATHOLOGY AND MEDICAL LABORATORY, 2014)
Tuberculosis (TB) is an infection caused by Mycobacterium tuberculosis and health problem and cause of death worldwide. MDR-TB occurs in patients who are inadequate and irregular in treatment. WHO strategy for MDR-TB is taking anti-tuberculosis (OAT) which has the effect of second-line heavier. Ethionamide one second-line OAT is administered orally and has a side effect of hypothyroidism. A cross-sectional descriptive study was conducted on 18 patients with MDR-TB from July 2012–March 2013. One patient has been excluded due to hypothyroidism. Increased TSH levels exceeded the cut-off occurred in 2 of 4 people after 1 month of treatment, 3 of 3 people after the 5th month of treatment, 1 of 4 people after 6 months of treatment and 1 of 3 people after month 9 treatment. Only 1 person who had increased levels of TSH>10 μIU/ mL. Conclusion: in patients with MDR-TB evaluation is required to determine the levels of TSH hypothyroidism.